Nano Photocatalytic Process Application of ZnO Nanoparticle and UV on Benzene Removal from Synthetic Air - Nassehinia, H.R.; Gholami, M.; Jonidi Jafari, A.; Esrafily, A. (Asian Journal of Chemistry, 2013)
Ornament painting and insects repellent solvents based on organic compounds, especially benzene compounds, were widely used in recent years. Exposure to gaseous benzene causes carcinogen and acute and chronic skin disease and even adverse effects on the nervous system. Photocatalytic systems are suitable for treating low concentration pollutants in air. The focus of this paper is on the photocatalytic degradation of benzene in photo reactor of ZnO catalyst by ultra violet radiation. The conventional sol-gel method was employed for the preparation of ZnO catalyst. The prepared ZnO sol-gel was coated by thin film dip-coating to deposit the catalyst on glass. UV lamps with a wavelength peak at 365 nm was employed as UV light source. ZnO thin film increased the photocatalytic activity due to the maximization of UV lamps illumination and increasing of retention time of benzene in the reactor. In this research, removal of benzene by ZnO and UV follows the zero order reactions.